A phytosociological study of Exbucklandia populnea species and its communities at highland forests of Cameron Highland - Ngaliman, Mohamad Pazlan (2018)
Phytosociology includes plant communities within the same environment, their floristic composition and development, and the social relationship between them. The information of the distribution of species as well as associations between species or groups of species could be achieved from a phytosociological study, which could lead to an important assessment of the vegetation. A vegetation study was carried out at Sg. Terla and Mentigi Forest Reserved, Cameron Highland, Pahang. The study area been describe as montane forest with attitude 1200m and above. A total of ten plots was established in this study area with size of five meters. The study including the canopy structure, species composition and richness. The phytosociological vegetation study was done followed the Braun Blanquet method (1964) and Fujiwara (1987). Result of the study shows 33 species belong to 29 genera and 23 families were found in study area. The most abundant family was Hamamelidaceae with 39 individual trees, and represent by one species in one genera namely Exbucklandia populnea. In addition, there was five species that was represent with only one individual in the study plots, namely, Daemonorops sp., Ficus benjamina, Licuala sp., Rutaceae sp., and Zyngiber sp..With the least number of species and individual, this species is considered as the most uncommon species (rare) within the study plots. The species communities in this area that have been identified is Lithocarpus rassa - Syzygium cerinum community and the second is Selaginella willdenowii - Helminthostachys zeylanica community. The different from this two communities that can be obtain is based on the slope of the area and the altitude. Indirectly, from the data that been obtain, less super tree have been found in the study area, which is because the plant in the montane forest have been adaptation to the surrounding habitats.